2011
DOI: 10.1029/2011jb008213
|View full text |Cite
|
Sign up to set email alerts
|

Seismic hazard in western Canada from GPS strain rates versus earthquake catalog

Abstract: [1] Probabilistic seismic hazard analyses (PSHA) are commonly based on frequencymagnitude statistics from 50-100 yearlong earthquake catalogs, assuming that these statistics are representative of the longer-term frequency of large earthquakes. We test an alternative PSHA approach in continental western Canada, including adjacent areas of northwestern U.S.A., using regional strain rates derived from 179 Global Positioning System (GPS) horizontal velocities. GPS strain rates are converted to earthquake statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 41 publications
3
52
0
Order By: Relevance
“…Likewise, the Fish Creek Mountains fault has a well-mapped surface trace to the east of the Coyote Creek fault (Figure 2). Strain rates can be indicative of the elastic energy accumulation in the crust, and thus directly related to seismic hazard (Elliott et al, 2016;Field et al, 1999;Mazzotti et al, 2011;Molnar, 1979;Riguzzi et al, 2012;Ward, 1998). The magnitude of this anomaly is comparable to that due to the San Andreas fault (Figure 3).…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, the Fish Creek Mountains fault has a well-mapped surface trace to the east of the Coyote Creek fault (Figure 2). Strain rates can be indicative of the elastic energy accumulation in the crust, and thus directly related to seismic hazard (Elliott et al, 2016;Field et al, 1999;Mazzotti et al, 2011;Molnar, 1979;Riguzzi et al, 2012;Ward, 1998). The magnitude of this anomaly is comparable to that due to the San Andreas fault (Figure 3).…”
Section: Discussionmentioning
confidence: 96%
“…Henton et al (2006) and Mazzotti et al (2011) showed that surface strain measured by GPS indicates strain rates are below the measurement error within Alberta and the Rocky Mountains. More to the west, in the Intramontane Belt, the values are also very low, yet in the coastal cordilleras, rates of about 10-15 mm yr −1 in the northeasterly direction with respect to stable North America are observed.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Flesch et al (2007) found that (deviatoric) stresses associated with the accommodation of relative plate motion are of the same order of magnitude as buoyancy forces (gravitational potential energy -GPE). The orientation of observed North American rotation, shortening in the Canadian Cordillera (Henton et al, 2006;Mazzotti et al, 2011), and GPE gradient orientation (Flesch et al, 2007) correspond to the observed average S Hmax azimuths in Alberta (see the rose diagram in Fig. 4).…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Horizontal strain rates are calculated on a regular 0.5 × 0.5 • grid using a Gaussian interpolation function with a 75 km half-width and taking into account each GPS sites uncertainty (cf., Mazzotti et al, 2011). The horizontal strain rate field (Fig.…”
Section: Velocity Solutionmentioning
confidence: 99%